Nova contribuiçao ao conhecimento da formação Rio Claro (T) na Folha Rio Claro (SP) - Perinotto, José Alexandre de Jesus [UNESP]; Etchebehere, Mario Lincoln de Carlos; Zaine, José Eduardo [UNESP]; Saad, Antonio Roberto [UNESP] (My University, 2006)
The Rio Claro Formation mainly occurs in the county of Rio Claro (SP) lying unconformably on Paleozoic and Mesozoic rocks. Its thickness is 30-40 m. It shows fine to coarse, regular to poor sorted, Triable sandstones and conglomerates with quartzite and quartz clasts in the base. Thin layers of mudstone occur interbeded. Stratigraphic maps had been elaborated in recent analyses allowing to improve the knowledge about the formation. The biggest thicknesses occur on the east part of the studied area. The coarse/fine clastic ratio map demonstrates that fine sediments are concentrated in the east side, and suggests the existence of barriers which conditioned perennial water body (or bodies) where decantation took place (east, south and southeast sides). The structural contour map of the Rio Claro Formation base indicates a NW/SE trough which was the main depositional axis. The integrated analysis demonstrates that the formation is formed by lacustrine, fluvial and debris flows deposits whose source area was located on NW side, with coalescent alluvial fans from where braided to psamitic meandering fluvial channels came. The location of the source area suggests no link with the Corumbataf River paleo-terraces.

A Formação Rio Claro ocorre em sua maior parte no município de Rio Claro (SP). Assenta-se discordantemente sobre rochas paleozóicas e mesozóicas. Sua espessura é de 30-40 m em poços da região. Apresenta arenitos finos a grossos, regular a mal selecionados, friáveis, tendo, na base, conglomerados com clastos de quartzito e quartzo. Intercaladas, ocorrem delgadas camadas de argilito. Em recentes análises, foi possível elaborar mapas estratigráficos que permitiram avançar no conhecimento da formação: as maiores espessuras ocorrem na porção leste da área de estudo; o mapa de razão clásticos grossos/finos indica a ocorrência preferencial de finos na região leste, sugerindo mecanismo de barramento, que condicionou a existência de corpo ou de corpos de água perene, com decantação de pelitos a leste, sul e sudeste; o mapa de contorno estrutural da base da formação define uma calha de direção NW/SE, que funcionou como eixo de deposição. A análise integrada indica que essa unidade contém depósitos lacustres, fluviais e de fluxos de detritos, com área-fonte a NW, com leques coalescentes, de onde derivavam canais entrelaçados a meandrantes psamíticos. O sentido de deposição (NW/SE) sugere que essa não corresponde a terraços (paleo-aluviões) do Rio Corumbataí.
Contribution to the knowledge of the Rio Claro Formation, Region of Rio Claro, State of São Paulo
Keywords: Rio Claro; Rio Claro formation; Tertiary; alluvial fan; conglomerate; contour map; formation mechanism; Mesozoic; Paleozoic; quartz; quartzite; sandstone; Brazil; Sao Paulo [Brazil]; South America